Investigating Metacognitive Awareness Of Reading Strategies To Strengthen Students' Performance In Reading Comprehension - Fitrisia, Dohra; Kok, Eng Tan; Yusuf, Yunisrina Qismullah (Penerbit Universiti Sains Malaysia, 2015)
This study was about the metacognitive awareness of reading strategies to enhance students' performance in reading comprehension. From five government secondary schools in Banda Aceh, Indonesia, 272 students in grade three participated in this research. Two standardised English reading comprehension tests from Ujian Nasional (UN, or National Examination) 2005/2006 and the Metacognitive Awareness of Reading Strategies Inventory (MARSI) by Mokhtari and Reichard were employed. The MARSI consisted of 30 items that measured MARS, which were divided into three categories: global reading strategies (13 items), problem solving reading strategies (8 items), and support reading strategies (9 items). The results indicated a weak positive relationship between MARS and scores in reading comprehension. No significant difference was found in the students' level of MARS between good and poor readers. It was also found that the level of MARS for problem solving reading strategy was than for global and support reading strategies. The findings suggest direct instruction in MARS may help students increase their attention to the reading process. Becoming aware of their own thinking as they read and solve problems allows students to seize the advantages of learning opportunities to become strategic and thoughtful readers.